2019
DOI: 10.1016/j.drugalcdep.2018.10.027
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of nonmedical use of prescription opioids during adolescence and subsequent substance use disorder symptoms in early midlife

Abstract: Background: This longitudinal study assesses characteristics associated with adolescents’ nonmedical use of prescription opioids (NMUPO) including: frequency, co-ingestion, motives, specific opioid type; sequence of initiation of medical use of prescription opioids and NMUPO in relationship to subsequent substance use disorder (SUD) symptoms. Methods: Twenty-one independent national cohorts of U.S. high school seniors (n = 8,373) were surveyed and followed 17 years from adolescence to age 35. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 54 publications
2
54
1
Order By: Relevance
“…15 Several characteristics associated with prescription opioid misuse (e.g., frequency, co-ingestion, multiple opioids) have been shown to increase the risk of SUD symptoms. 16 While most youth cease prescription opioid misuse over time, there is evidence that about one-third continue to misuse prescription opioids, placing themselves at high risk for adverse consequences such as overdose and SUD. 12,16 Prescription stimulants:…”
Section: Prescription Opioidsmentioning
confidence: 99%
“…15 Several characteristics associated with prescription opioid misuse (e.g., frequency, co-ingestion, multiple opioids) have been shown to increase the risk of SUD symptoms. 16 While most youth cease prescription opioid misuse over time, there is evidence that about one-third continue to misuse prescription opioids, placing themselves at high risk for adverse consequences such as overdose and SUD. 12,16 Prescription stimulants:…”
Section: Prescription Opioidsmentioning
confidence: 99%
“…[18][19][20][21][22] At the same time, exposure to opioids has been associated with future opioid misuse. 4,23 This poses a great challenge for providers in managing both short-and long-term welfare of patients. We therefore find it imperative to describe and understand current opioid administration practices during hospitalization so opportunities for improvement in patient care can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of opioid-related hospitalization and death are increasing, particularly among children, [1][2][3] and significant national attention is focused on opioid misuse. Previous studies have shown that opioid addiction frequently begins in adolescence or young adulthood, 4 and onequarter to one-third of young adults who report nonmedical prescription opioid use had an earlier history of prescribed medical opioid use. [5][6][7] Unintentional injury is the leading cause of death and disability among children, with more than 8 million children treated for injury in emergency departments (ED) each year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…148 were the highest for adolescents who either: 1) reported the medical use of prescription opioids after initiating NMUPO or 2) reported only NMUPO. 149 Furthermore, adolescents in these two groups had significantly higher odds of alcohol use disorder (AUD), cannabis use disorder (CUD), and the other drug use disorders (ODUD) compared to adolescents who had no history of medical or nonmedical use of prescription opioids (refer to Table 2.3 for all adjusted odds ratios). 149 2.47 (1.74, 3.52)** (n = 7158) b p < 0.05*, p < 0.001** a All analyses control for race/ethnicity, sex, the highest level of parental education, geographic region, metropolitan statistical area, baseline cohort year, and baseline measures of past-year alcohol use, past-year marijuana use, and past-year other drug use.…”
Section: Prescription Stimulantsmentioning
confidence: 99%